Towards a design model for things in agents of Things - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C.; Ahmad A. (Association for Computing Machinery, 2023)
Cloud computing; Hardware; Internet; Reconfigurable hardware; Software agents; Intelligent software agent; Internet of thing (IOT); Machine-to-machine communications; Reasoning ability; Reasoning capabilities; Self-reasoning; Software analysis; Value added service; Internet of things